2023
DOI: 10.3389/fpls.2022.1115513
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of MADS-box gene family in the U’s triangle species and targeted mutagenesis of BnaAG homologs to explore its role in floral organ identity in Brassica napus

Abstract: MADS-box transcription factors play an important role in regulating floral organ development and participate in environmental responses. To date, the MADS-box gene family has been widely identified in Brassica rapa (B. rapa), Brassica oleracea (B. oleracea), and Brassica napus (B. napus); however, there are no analogous reports in Brassica nigra (B. nigra), Brassica juncea (B. juncea), and Brassica carinata (B. carinata). In this study, a whole-genome survey of the MADS-box gene family was performed for the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…It is suggested that the MADS-box gene containing K-box domain has a certain regulatory effect on auxin and gibberellin, which affects the growth and development of maize. Studies have found that MADS-box gene is involved in a variety of hormone processes, indicating that plant hormones regulate MADS-box gene in a variety of ways, and there may be synergism or antagonism among different plant hormones Song et al, 2023). At present, the regulatory role of MADS-box in some plant hormones (such as ABA, BR) and drought stress signal transduction has been proved (Duan et al, 2006;Shao et al, 2010;Ma, 2022), but its role in other hormones and stress signal transduction has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the MADS-box gene containing K-box domain has a certain regulatory effect on auxin and gibberellin, which affects the growth and development of maize. Studies have found that MADS-box gene is involved in a variety of hormone processes, indicating that plant hormones regulate MADS-box gene in a variety of ways, and there may be synergism or antagonism among different plant hormones Song et al, 2023). At present, the regulatory role of MADS-box in some plant hormones (such as ABA, BR) and drought stress signal transduction has been proved (Duan et al, 2006;Shao et al, 2010;Ma, 2022), but its role in other hormones and stress signal transduction has not been reported.…”
Section: Discussionmentioning
confidence: 99%